Spectral Computed Tomography Imaging of Gastric Schwannoma and Gastric Stromal Tumor. Issue 3 (May 2017) - Liu, Jianli; Chai, Yanjun; Zhou, Junlin; Dong, Chi; Zhang, Wenjuan; Liu, Bin
Objective: Gastric schwannomas (GSs) and gastrointestinal stromal tumors (GSTs) are grossly similar submucosal neoplasms with different prognoses. We explored the value of spectral computed tomography (CT) to distinguish between them. Methods: Patients diagnosed with GS or GST at Lanzhou University Second Hospital, China, between May 2013 and June 2015 were included retrospectively. The subjects underwent spectral CT examination before surgery and had histologically confirmed diagnosis of GS or GST. Results: Twelve patients with GS (3 men; 9 women; mean [SD] age, 47.0 [11.5] years) and 20 with GST (7 men; 13 women; mean [SD] age, 54.7 [9.9]) showed significant differences in terms of arterial phase (AP) at 70 keV ( P < 0.001), portal phase (PP) at 70 keV ( P = 0.002), AP iodine concentration, PP iodine concentration, AP water concentration, AP slope of spectral curve, and PP slope of spectral curve (all P < 0.001). Conclusions: Spectral CT may be useful for noninvasive diagnosis of submucosal tumors.